Coeliac disease in the elderly in a tertiary centre. (2nd October 2016) - Tortora, Raffaella; Zingone, Fabiana; Rispo, Antonio; Bucci, Cristina; Capone, Pietro; Imperatore, Nicola; Caporaso, Nicola; D'Agosto, Domenico; Ciacci, Carolina
Abstract: Introduction and aims: Coeliac disease (CD) was believed to be a childhood disease while it can affect any age. Aim: to evaluate the prevalence of CD in elderly population, recording the main clinical features of this group respect to young patients. Methods: We retrospectively analysed the prevalence of CD in an elderly population from 1970 to 2015. We divided patients into three age-groups (group A: 18–34 years; group B: 35–64 years; group C: ≥65 years) and compared them regarding baseline anthropometric and serological variables, clinical features at diagnosis, diagnostic mode, associated autoimmune diseases, and CD-related neoplastic complications. Results: We made 2812 CD diagnoses in adults: 2.5% of them were ≥65 years at diagnosis. When comparing the three groups, we found no differences in sex, haemoglobin, serum iron, albumin, and anti-tissue transglutaminase (anti-tTG) ( p = NS) while as expected, we found higher values of cholesterol, glycaemia, and triglycerides in older patients ( p < 0.0001). Elderly had a higher risk of being diagnosed with malabsorption symptoms compared to younger patients (OR 2.20, 95%CI 1.3–3.74). No difference in the risk of autoimmune CD-related diseases was seen among groups. Furthermore, we observed 16 neoplastic complications, 13 of them happened in the patients diagnosed with CD aged 35–64 years. The number of CD diagnoses increased over time, particularly in elderly. Conclusion: CD diagnosis in elderly population is quite uncommon although not rare. Elderly CD patients have a higher risk of being diagnosed with malabsorption symptoms than younger patients but without increased risk of autoimmune and neoplastic complications.